Cidades criativas e desenvolvimento regional : o caso de Vitória-ES - Comério, Larissa de Melo (2014)
The present work intends to engage in discussion of the elements that make up the creative economy, therefore, uses different concepts of creativity, creative industries and creative cities. The term creative economy appeared in 2001 with the book of John Howkins, but the basic idea was presented in the Creative Nation study conducted by the Australian government in 1994. Since then, several countries have adopted the concept as an instrument to promote economic and social development. Thus, the combination of a creative and a development economy is linked, therefore, to the recognition that human creativity can be an economic asset (Reis, 2012). Different countries and regions can use this approach with the objective to achieve positive effects on employment and as a tool for the promoting social inclusion. The discussion is recent in Brazil, one of the pioneering studies was developed by the Federation of Industries of the State of Rio de Janeiro ( FIRJAN ) entitled "The Chain of Creative Industry in Brazil". From that job and the database of the Department of Tourism, Work and Income from the City of Vitória was possible to develop a spatial study of creative enterprises to the county. Then it was concluded that the deconcentration of creative enterprises in different regions of the municipality must be one of the goals pursued for the city to become a more collaborative and cohesive space.